Sequences important for heterokaryon incompatibility function in MAT A-1 of Neurospora crassa - Patrick K.T. Shiu; N. Louise Glass (Fungal Genetics Reports, 2006)
Using chimeric constructs between the Neurospora crassa mat A-1 gene and the Podospora anserina FMR1 gene, we identified the amino acids important for the heterokaryon incompatibility function in the mating-type protein MAT A-1.